Simulation Of Blood Flow Through Transcatheter Heart Valve (Thv) Using Ansys Fluid Structure Interaction - Juma’at, Mohamad Haziq (Universiti Sains Malaysia, 2019)
As transcatheter heart valve replacement (THVR) progressively became an alternative to surgical heart valve (SHV) from it first implantation in 2000, numerous research and lots of improvement has been made and still on going until now. However, does the effectiveness of the transcatheter heart valve (THV) is on par with the mechanical heart valve and other prosthetic heart valves. In this research project, the three-dimensional 29 mm SAPIEN XT inside the left side heart is designed and simulated using computational fluid dynamics software. The simulation is carried out by using ANSYS Fluid Structural Interaction (FSI) to analyse the fluid field, velocity, pressure, vortices and wall shear stress obtained. The simulation is validated by Particle Image Velocimetry (PIV) experiment by comparing the prosthetic mitral valve inlet velocity, outlet velocity and Doppler Velocity Index (DVI) of the THV.